PSYCHOLOGICAL EFFECTS OF COLOR AND COLOR THERAPY: रंगो का मनोवैज्ञानिक प्रभाव एवम रंग चिकित्सा - Sugandhi, Pratima; Neema, Rajashree (International Journal of Research -GRANTHAALAYAH, 2014)
Man is the best masterpiece of God and color is the best gift of creation. It is such an offering of nature that makes life more attractive. By the nature of nature, man determines his life and tries to live a healthy life by establishing this community. Just as the heat and light of the sun has an effect on our life, the colors have an effect on our body and mind. The importance of colors is not limited only to the growth of beauty, but it also has a direct impact on the nature of man, his future and his health. मनुष्य ईश्वर की सर्व श्रेष्ठ कृति है और रंग सृष्टि का बेहतरीन उपहार है । यह प्रकृति की ऐसी भेंट है जिससे जीवन और अधिक आर्कषक बनता है । प्रकृति के सांिनध्य से मनुष्य अपने जीवन को निर्धारित करता है और इस सामाजन्स्य को स्थापित करते हुए स्वस्थ जीवन जीने का प्रयास करता है। जैसे सूरज के ताप व प्रकाश का हमारे जीवन पर प्रभाव पड़ता है वैसा ही रंगो का प्रभाव हमारे शरीर व मन पर पड़ता है। रंगो का महत्व केवल सौन्दर्य वृद्धि तक सीमित नहीं है अपितु मनुष्य के स्वभाव उसके भविष्य एवम उसके स्वास्थ्य पर भी इसका सीधा प्रभाव पड़ता है ।